Transparency and fairness in the European capital market - Hans-Joachim Voth (Hans-Böckler-Stiftung, 2008)
Will the finance markets experience a crash when some of the big hedge funds go bust? And will we soon be seeing large numbers of German businesses taken over by private investors who then dismiss droves of employees and relocate production abroad so that expectations of enormously high yields can be fulfilled? It is these questions that the report investigates. It describes the background and incentives that have led to a vast inflow of money into private equity and hedge funds, explains just how good their performance as an investment vehicle really is, and analyses the opportunities and risks for the stability of the finance system and the growth implications for the German economy. The focus is on regulatory proposals and in this context the report advocates a departure from 'soapbox speeches'. There are an enormous number of practical hurdles standing in the way of tighter regulation and they may not be naively ignored. A direct regulation of funds with domiciles on offshore islands is not enforceable. But even without support from the Anglo Saxon partners, European policy makers can do much to implement more meaningful regulations. An important starting point is the regulation of the banks: the granting of loans must be handled more wisely and with more restraint. The report makes a number of practical proposals, suggesting ways how the many increasingly threatening dangers can be eliminated. – – Kommt der große Crash an den Finanzmärkten, wenn einige große Hedge-Fonds pleite gehen? Und werden demnächst deutsche Unternehmen in großer Zahl von Privatinvestoren übernommen, die Mitarbeiter scharenweise entlassen, die Produktion ins Ausland verlagert, damit enorm hohe Renditeerwartungen erfüllt werden können? Das Gutachten geht diesen Fragen nach. Es schildert den Hintergrund und die Anreize, die zu einem enormen Mittelzufluss in Private Equity - und Hedge-Fonds geführt haben, legt dar, wie gut deren Performance als Anlagevehikel wirklich ist, und analysiert die Chancen und Gefahren für die Stabilität des Finanzsystems und die Wachstumsimplikationen für die deutsche Volkswirtschaft. Das Hauptaugenmerk liegt auf Regulierungsvorschlägen. Dabei plädiert das Gutachten für einen "Abschied von den Sonntagsreden". Die praktischen Hürden für eine schärfere Regulierung sind enorm, und dürfen nicht blauäugig ignoriert werden. Eine direkte Regulierung der Fonds mit Sitz auf Offshore-Inseln ist nicht durchsetzbar. Dennoch kann die europäische Politik - auch ohne Schützenhilfe der angelsächsischen Partner - viel tun, um für sinnvollere Regeln zu sorgen. Ein Hauptansatzpunkt ist dabei die Bankenregulierung. Die Kreditvergabe der Banken muss klüger und maßvoller gesteuert werden. Das Gutachten macht eine Reihe von praktischen Vorschlägen, wie so viele zunehmend bedrohliche Gefahrenpunkte beseitigt werden können.
Keywords: 330; Finanzmarkt; Hedgefonds; Private Equity; Regulierung; EU-Staaten